126 Maxwell Lectureship: Large Scale Practical Nutrition Research Sharing: Feeding the E. Coli Challenged Pig: What we Have Learned to Date. (12th April 2022) - Gerhart, Mandy J; Carrender, Brittany; Coble, Kyle
Abstract: Over the past couple of years there has been a marked increase in the amount of E. coli outbreaks observed during the nursery phase of production. This is a multi-disciplinary issue and requires a holistic understanding of all possible contributing factors and input from production, vet, and nutrition teams. For the purposes of this presentation, we will focus on what potential impacts nutrition may have on E. coli . Within our production system we have made numerous modifications to our nursery diets to try and reduce mortality and help ameliorate scours associated with E. coli . To better understand what impacts our diet modifications have made on performance, fecal consistency, and mortality we have used a combination of monitoring closeouts, field trials, and challenge studies conducted at our research facility. In the field we have investigated the effects of reducing SID lysine, increasing oats, various feed additives and medication strategies. We took these questions to our research barn where we looked at IDF:SDF ratios, crude protein by oat, lactose by SBM, and lactose level by phase. To ensure the answers from our research barn aligned with field conditions, each trial utilized multiple sow sources and a challenge protocol where pigs were inoculated with E. coli . This challenge model has been successful in eliciting an E. coli outbreak in each trial where it was applied, providing us with a robust tool to mimic field scenarios in a typical high-health, low mortality, research facility. To complement what we were learning with controlled research we have also completed numerous validation experiments in the field, using an 8-week, two-treatment approach. To date, we have not found the silver bullet when it comes to eliminating E. coli issues in the nursery; however, we have learned some valuable lessons as to what does and doesn't work for our genetics, facilities, and producers.